خطوطِ اقبال متنی تنقید کے تناظر میں: تحقیدی مطالعہ: Iqbal’s Letters in the Context of Textual Criticism: A Research Review - ہاشمی طالب حسین (Tashkeel e Jadeed, 2024)
The literal meaning of the text is the original words of the author, the original text of the book, the text of the reservoir on the page of the book, the middle part of the book, cloth or road, the middle, the back, the , the middle part of two pillars. The term meaning of the text is something like A text or document written in a language with which the reader or writer is familiar, understands, and wishes to organize or edit. The term textual criticism is also used in a limited sense in editing text. In this case, it refers to the description of the external and internal features of the text. And the decoration means its decoration, its intersection, ruler, number of pages, blanks and pages, characteristics and condition of the paper, script, calligraphy, pen, lighting characteristics, seals and their Statement of numbers and description, signature, beginning, ending, and counting. Several collections of Allama Iqbal's poetry and prose works and schools have been published, but none of these collections can be said to be the final word in the chapter of his writings, because even now, sometimes and somewhere, some of his unpublished works are published.